TANTANGAN MEWUJUDKAN KESETARAAN GENDER DALAM BUDAYA PATRIARKI - Nanang Hasan Susanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
Although the issue of gender equality tobe a demand in almost all countries, but the fact is not easy to achieve gender equality. This appearance infected the construc of cultural patriarchy since long time ago for discriminating roles of men and women. This Social Construct go on from generation to generation. Actually, there is still hope for realize the gender equality, although it requires a process. Among them is through education by providing adequate access to women, to exercise control over every policy of gender bias, involving women to provide participation, and provide equitable benefits between men and women.